ANALISIS PENERAPAN PEMBUKUAN KEUANGAN DIGITAL â€œBUKU WARUNGâ€ SEDERHANA PADA TOKO PERTANIAN WISMA TANI DI DESA GLINGGANG KEC. SAMPUNG - Tikasari, Eka; Firdaus Mustoffa, Ardyan (JURNAL ILMIAH EDUNOMIKA, 2024)
Financial reports for MSME players play a role in ensuring that financial management is running well and as a reference that the business is healthy, marked by smooth financial flows. Many MSMEs are still unfamiliar with financial bookkeeping because it is considered something complicated. Apart from that, quite a few MSME players have implemented financial bookkeeping, even if it is simple. Simple financial bookkeeping still encounters obstacles, so efforts are made to use applications, one of which is the Bukuwarung application which can be accessed via smartphone. This research aims to analyze the application of digital bookkeeping through the Buku Warung application at the Wisma Tani Store. The method in this research is descriptive qualitative with a phenomenological approach. Data collection was carried out by direct interviews with the owner of the Wisma Tani Agricultural Shop, Ds. Glinggang and documentation for using the BukuWarung application. Data analysis applies the Miles and Hubberman model which includes data reduction, data presentation, and drawing conclusions. The Bukuwarung application is a financial recording application used by MSMEs in their financial reporting. According to the Wisma Tani Agricultural Shop UMKM player, using the Bukuwarung application makes it easier to keep book-keeping for his business. Profit and loss statements are easier to understand and recorded neatly. Bukuwarung has a feature, namely recording income and expenses, which ensures that cash flow remains well recorded and provides business bookkeeping reports that can be accessed daily, weekly or monthly, making it easier for business owners to monitor the financial health of their business in real-time.. Keywords : Digital Financial Bookkeeping BukuWarung, Financial Reports, and MSEMs (Micro, Small, and Medium Enterprises)